ACTIVATION OF CELLS FROM HYPOTHALAMIC STRUCTURES AFTER INJECTION OF ANTIGENS DIFFERENT IN THEIR NATURE (by the c-Fos expression) - S. V. Perekrest (SPb RAACI, 2014)
Abstract. Activation levels of hypothalamic structures (AHN, PVH, DMH, VMH, LHA, PH) were analyzed within first hours after injection of antigens [lipopolysaccharide (LPS) and bovine serum albumine [BSA]). For all investigated hypothalamic structures, an increase of c-Fos positive cells numbers was observed after injection of the antigens, as compared to the controls. LPS injection caused activation of more multiple neuron populations. AHN, PVH, LHA, and PH structures exhibited the highest levels of c-Fos activation upon LPS application. BSA injection induced activation of lesser cells quantities, but their enrichment in c-Fos protein was higher, thus resulting into increased optical density of VMH, LHA and PH neurons. Hence, the present work has shown that activation pattern of hypothalamic structures differs upon application of antigens that are different by their origin.